Direct production of 4‐hydroxybenzoic acid from cellulose using cellulase‐displaying Pichia pastoris. Issue 4 (4th January 2023) - Inokuma, Kentaro; Miyamoto, Shunya; Morinaga, Kohei; Kobayashi, Yuma; Kumokita, Ryota; Bamba, Takahiro; Ito, Yoichiro; Kondo, Akihiko; Hasunuma, Tomohisa
Abstract: 4‐hydroxybenzoic acid (4‐HBA) is an industrially important aromatic compound, and there is an urgent need to establish a bioprocess to produce this compound in a sustainable and environmentally friendly manner from renewable feedstocks such as cellulosic biomass. Here, we developed a bioprocess to directly produce 4‐HBA from cellulose using a recombinant Pichia pastoris strain that displays heterologous cellulolytic enzymes on its cell surface via the glycosylphosphatidylinositol (GPI)‐anchoring system. β‐glucosidase (BGL) from Aspergillus aculeatus, endoglucanase (EG) from Trichoderma reesei, and cellobiohydrolase (CBH) from Talaromyces emersonii were co‐displayed on the cell surface of P. pastoris using an appropriate GPI‐anchoring domain for each enzyme. The cell‐surface cellulase activity was further enhanced using P. pastoris SPI1 promoter‐ and secretion signal sequences. The resulting strains efficiently hydrolyzed phosphoric acid swollen cellulose (PASC) to glucose. Then, we expressed a highly 4‐HBA‐resistant chorismate pyruvate‐lyase (UbiC) from Providencia rustigianii in the cellulase‐displaying strain. This strain produced 975 mg/L of 4‐HBA from PASC, which corresponding to 36.8% of the theoretical maximum yield, after 96 h of batch fermentation without the addition of commercial cellulase. This 4‐HBA yield was over two times higher than that obtained from glucose (12.3% of the theoretical maximum yield). To our knowledge, this is the first report on the direct production of an aromatic compound from cellulose using cellulase‐displaying yeast. Abstract : A recombinant Pichia pastoris strain co‐displaying three cellulases and expressing chorismate pyruvate‐lyase was constructed for direct production of 4‐hydroxybenzoic acid (4‐HBA) from cellulose. This strain produced 975 mg/L of 4‐HBA from phosphoric acid swollen cellulose, with a yield of 11.6% after 96 h of batch fermentation without commercial cellulase addition.